Anti-stress Role of Cyanocobalamin in Heat- induced Weight Loss in Albino Rats (Medical Forum Monthly, 2024)
Objective: To determine the deleterious effects of heat-stress on the body weight and to evaluate the anti – stress role of the Cyanacobalamin. Study Design: An Experimental study Place and Duration of the Study: Department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi from November 2010 to February 2011. Materials and Methods: Forty five Albino rats (180-200 grams) were selected and divided into group A (Control), group B (Heat - induced) and group C (Protective). Each group was further subdivided into three subgroups, based on the period of the study. The animals of the subgroups B and C received heat and the temperature was set at 42 C for six hours daily. Group C (C1, C2 and C3) animals were protected with Cyanocobalamin at the dosage of 0.8 mg/ kg of body weight intraperitonealy, two hours before heat induction. All the animals were weighed before the commencement of the study. Blood samples were collected for the hormonal assay of plasma ACTH level. Results: Heat –stress and its consequences significantly decrease the body weight in group B animals. It could be due to hyper activation of the HPA and is and resultant ACTH corticosterone secretions causecatabolism of muscle and other bodily proteins. The prophylactic use of Cyanocobalamin group C animals by its cytoprotective of and anti-apoptotic role significantly increase the body weight and restore ACTH secretions near to normal. Conclusion: Findings of the current study conclude that Cyanocobalamin is beneficial to alleviate the detrimental effects of the heat-stress.